Evropská ústava - Nedobitá, Alena (Univerzita Pardubice, 2006)
Tématem této diplomové práce je problém Evropské ústavy. Práce je rozdělena do šesti hlavních kapitol. V první kapitole se zabývám historickým vývojem Evropské ústavní smlouvy. Jsou zde popsány smlouvy a summity, které předcházely vzniku Evropské ústavy, ratifikační proces a současná situace. Druhá část popisuje důvody vzniku Evropské ústavní smlouvy. Třetí kapitola je zaměřena na Konvent a jeho složení, práci a také činnost českých zástupců. Čtvrtá kapitola popisuje jednotlivé části Ústavy a analyzuje změny, které by přijetí Ústavy přineslo. Předposlední pátá kapitola se zabývá slučitelností Evropské ústavy s ústavou V. Francouzské republiky. Šestá kapitola je zaměřena na vývoj německé ústavnosti v závislosti na vývoji evropské integrace.

The topic of this thesis is: "European constitution". The thesis consists of six chapters. The first one deals with historical evolution of the European constitution. Treaty pacts and summits which have preceded to the rise of the European constitution are described here. The second part describes the reasons of the existence of the European constitution. I focused on the Convention and its composition, its working process and also the activities of the Czech representatives, in the third chapter. The fourth chapter summaries the particular parts of the Constitution and analyses changes which will bring the passage of the constitution. The five chapter concerns in the European constitution recompatibility with the constitution of French Republic. The last chapter concerns in the evolution of the german constitutionality depending on European integration.
The European constitution
Keywords: European Union; European constitution; Convention; The Charter of fundamental rights of the Union; Summit EU; Process of ratification; The constituion of French Republic; Evropská Unie; evropská ústava; Konvent; Listina základních práv Unie; Summit EU; Ratifikační proces; Ústava Francouzské republiky